The Systemic Theory of Living Systems and Relevance to CAM: the Theory (Part III) - Olalde Rangel, José A. (Oxford University Press, 2005)
Western medical science lacks a solid philosophical and theoretical approach to disease cognition and therapeutics. My first two articles provided a framework for a humane medicine based on Modern Biophysics. Its precepts encompass modern therapeutics and CAM. Modern Biophysics and its concepts are presently missing in medicine, whether orthodox or CAM, albeit they probably provide the long sought explanation that bridges the abyss between East and West. Key points that differentiate Systemic from other systems' approaches are ‘Intelligence’, ‘Energy’ and the objective ‘to survive’. The General System Theory (GST) took a forward step by proposing a departure from the mechanistic biological concept—of analyzing parts and processes in isolation—and brought us towards an organismic model. GST examines the system's components and results of their interaction. However, GST still does not go far enough. GST assumes ‘Self-Organization’ as a spontaneous phenomenon, ignoring a causative entity or central controller to all systems: Intelligence. It also neglects ‘Survive’ as the directional motivation common to any living system, and scarcely assigns ‘Energy’ its true inherent value. These three parameters, Intelligence, Energy and Survive, are vital variables to be considered, in our human quest, if we are to achieve a unified theory of life.